“God, Why Did this Happen to Me?”: Three Perspectives on Theodicy - Bradshaw, Anna (Journal of pastoral care & counseling, 2003)
This article closely examines the way three people dealt with the theodicy question. The three study subjects participated in extended interviews about their religious beliefs and activities, past and present. The interviews were summarized and analyzed to identify the person's religious resources, statements about theodicy, and mental well-being. The subjects' comments highlight the unique and diverse ways in which people wrestle with theodicy. They also indicate that dealing with the question can extend over many years. Implications for ministry are discussed.